A rare B cell clonotype imprinted by ancestral SARS-CoV-2 develops cross-sarbecovirus neutralization in immune recalls - Xixian Chen; Ling Li; Ruiping Du; Zuowei Wang; Yunjian Li; Yi Sun; Rongrong Qin; Hualong Feng; Lin Hu; Xuanyi Chen; Maosheng Lu; Xueyan Huang; et al. (Cell Reports)
Summary: The ultimate potential of B cells imprinted by ancestral SARS-CoV-2 in developing neutralizing breadth and potency remains to be explored. Here, we longitudinally tracked B cells that recognize the wild-type spike in two individuals who were repeatedly infected by Omicron variants after receiving prototype mRNA vaccines. Functional and genetic analysis of 632 monoclonal antibodies (mAbs) from those B cells reveals that mAbs cloned after a second infection have dramatically enhanced neutralizing breadth and potency due to immune recalls. Among the eleven mAbs that broadly neutralize SARS-CoV-2 variants from the wild type to KP.3, five mAbs are classified into public clonotypes encoded by IGHV3-53 or IGHV3-66, whereas the rest belong to a rare clonotype encoded by IGHV3-74. Notably, IGHV3-74 mAbs can also potently neutralize other sarbecoviruses by targeting a non-dominant epitope partially overlapping with receptor-binding domain (RBD)-3 and RBD-5. These results support that ancestral SARS-CoV-2 immune imprinting can be harnessed in developing pan-SARS-CoV-2 and even cross-sarbecovirus vaccines.